2017
DOI: 10.1111/apa.13798
|View full text |Cite
|
Sign up to set email alerts
|

Parents' presence and parent–infant closeness in 11 neonatal intensive care units in six European countries vary between and within the countries

Abstract: AimLittle is known about the amount of physical parent–infant closeness in neonatal intensive care units (NICUs), and this study explored that issue in six European countries.MethodsThe parents of 328 preterm infants were recruited in 11 NICUs in Finland, Estonia, Sweden, Norway, Italy and Spain. They filled in daily diaries about how much time they spent in the NICU, in skin‐to‐skin contact (SSC) and holding their babies in the first two weeks of their hospitalisation.ResultsThe parents' NICU presence varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 33 publications
12
119
6
2
Order By: Relevance
“…There is evidence of improved clinical stability during hospitalisation and of better short‐ and long‐term outcome if SSC and family‐centred care are practiced on a daily basis . Both our and other studies concluded that SFR care facilitate early and prolonged parental presence and involvement, and Lester et al. suggested that these factors, together with developmental support, were the main mediators of the positive effects of SFR care.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…There is evidence of improved clinical stability during hospitalisation and of better short‐ and long‐term outcome if SSC and family‐centred care are practiced on a daily basis . Both our and other studies concluded that SFR care facilitate early and prolonged parental presence and involvement, and Lester et al. suggested that these factors, together with developmental support, were the main mediators of the positive effects of SFR care.…”
Section: Discussionsupporting
confidence: 53%
“…Involvement of parents , and family‐centred care with parents as primary caregivers, has been associated with faster attainment of full enteral feeds and weight gain . As opposed to open‐bay (OB) units, single‐family room (SFR) units protect the infant and parents from environmental stress and offer more privacy, which may facilitate long‐term parent–infant closeness and skin‐to‐skin contact (SSC) . SFR design has been associated with more hours of maternal presence improved weight gain , earlier feeding , reduced risk of infection and earlier discharge and improved neurobehavioral and pulmonary outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings show that a majority of Swedish neonatal units provide opportunities for infant‐parent closeness, that is letting the parents stay with their infant day and night. Having the opportunity to stay overnight and/or having a single‐family room is not only positive for parental presence but also for the initiation and duration of skin‐to‐skin contact . A single‐family room is also a space where parents are more likely to feel emotionally close, attuned to their infant's needs and emotionally supported by staff .…”
Section: Discussionmentioning
confidence: 99%
“…Infant, parent, and environmental characteristics associated with preterm birth also may impact parental ability to engage in didactic caregiving due to parent–infant separation (Raiskila et al., ) and focus on the infant's survival (Hall, Kronberg, Aagaard, & Brinchmann, ). Therefore, didactic caregiving may be more relevant for parents of preterm infants postdischarge when their infants’ health condition has improved and parents assume full responsibility of care (Boykova, ).…”
Section: Introductionmentioning
confidence: 99%